PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Ade Susanti; Sukur; Ayu Purnasari (Mat-Edukasia, 2023)
The purpose of this study was to find out and describe the mathematical communication abilities of studeents whho were taughte usinge tthe group investigation typpe cooperatiive learniing modell bettter thann those taught by conventional learning in class IX students of SMP N 43 Merangin academic year 2022/2023. Thiis sutudy useed a quantitative approoach to the eksperimental metthode with aa posst-tesst only ccontrol desiign. The poopulation used iin thiis studyy weere class IX studennts oof SMP N 43 Merangin which consisted of 4 classes totaling 111 students. Way of taking samples using sample random sampliing techniquee. Data collectionn techniquess usingg testss in the forrm of descriptions which amount to 3 questions. Bassed on tthe resullts of the analysiis, the averagee vallue of the experimental cllass using the group investigation cooperative learning model was 5,35 and 64,44 in the conttrol cllass. From the resullts of datta analysiis, the normaliity test and homogeneiity test were carriied out, because the datta was normallly distriibuted and homogenneous, the hypothesiis test usiing the t-test was obtained thitung > ttabel or 1,771 > 1,675 it cann be councluded thaat the mathematical communation skills taught using the group investiigation type cooperatiive learniing modell are bettter tthan those taught by conventiional learniing of class IX students of SMP N 43 Merangin